Phytochemical Analysis of Soursop Peel, With the Extraction and Characterization of its Oil - Ezeiheukwu, Chika Mary; Okongwu, Dozie John (EduMatika: Jurnal MIPA, 2024)
Soursop (Annona muricata) peels was analysed for its proximate composition. It was found to contain 3.2 % dark green oil, 10.65 % crude protein, 21.3% moisture, 3.8 % ash, 12.69 % crude fiber, 31.31 % carbohydrates and 4.40 % ash. The elemental composition of the peel was determined, using Atomic Absorption Spectroscopy. It was found to contain Calcium (32.45 mg/100 g), magnesium (48.23 mg/100 g), zinc (125.15 mg/100 g), phosphorus (128.24 mg/100 g), iron (72.52 mg/100 g) and manganese (3.82 mg/100 g). Extraction of oil from the peel was also carried out using sohxlet extraction method. Some chemical Characteristics of the oil was determined. The result showed that the oil have a saponification value of 131.84 mg, iodine value of 66.68 mg/100 g, free fatty acid value of 3.64 mg, and oleic acid value of 0.1889 mg.